Constructing the CEO Personal Brand: The Case of Four Pioneering CEOs in Turkey - Erdogmus, Nihat; Esen, Emel (PALGRAVE MACMILLAN LTD, 2018)
CEOs are high-profile figureheads who have a critical role in their organization. Because of their high impact on firm performance and brands, stakeholders and the public follow them. The main purpose of this study is to explore pioneering Turk CEOs' construction of the CEO brand. The study focuses on the determinants and process of CEO branding and relies on content analysis of four CEOs' biographies using purposeful sampling. The comparative case study method was conducted using a grounded approach. As a result of the study, CEOs' career background, leadership in change, impression management, and firm brand became the determinants for the CEO brand building process. In this process, career background provides an advantage to leadership in change, and impression management mediates the relationship between leadership in change (performance) and CEO branding.
Keywords: Personal branding; CEO brand; CEO brand building; Grounded theory; IDENTITY; REPUTATION; MANAGEMENT; PRESS; MEDIA; BOARD; MODEL; Business & Economics